The Effect of Using AI-Based Learning Media on the Learning Motivation of Students in the Sociology Education Study Program at PGRI University of Sumatera Barat - Tarida Anggina; Faishal Yasin; Yanti Sri Wahyuni (Darul Yasin Al Sys, 2026)
The increasing integration of artificial intelligence (AI)-based learning media into higher education offers students greater access to information and assistance in understanding course material and completing assignments. However, inappropriate use may undermine learning independence, engagement, and responsibility. This study examined the effect of AI-based learning media on the learning motivation of students in the Sociology Education Study Program at Universitas PGRI Sumatera Barat. Grounded in Maslow’s Hierarchy of Needs Theory, the study employed a quantitative associative design. The population comprised 170 students from the 2022–2025 cohorts, from whom 65 participants were selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using descriptive statistics, normality and linearity tests, simple linear regression, t- and F-tests, and the coefficient of determination in IBM SPSS Statistics 21. The results showed that AI-based learning media positively and significantly predicted students’ learning motivation, as indicated by the regression equation Y = 42.309 + 0.516X and a significance value of 0.003 (p < 0.05). The correlation coefficient (R = 0.365) indicated a low positive relationship, while the coefficient of determination (R² = 0.133) showed that AI-based learning media accounted for 13.3% of the variance in learning motivation, with the remaining 86.7% attributable to other factors. These findings indicate that AI-based learning media can support students’ motivation when used appropriately, critically, and responsibly. The study underscores the importance of strengthening digital literacy and positioning AI as a learning support tool rather than a substitute for students’ independence and critical thinking.